(untitled) (Teología, 2018)
The author introduces Monseñor Pironio who, at the time was Secretary of the II Conference of the Latin American Episcopate in Medellín. He has been very important for this ecclesiastic event and his contributions have given a frame of reference to the critical thought of the shepherds gathered there. Due to his actions it did not remain subject to those days but also to the fact that he was an enthusiastic communicator of its ’spirit’ and, at the same time defender of an authentic interpretation. During all his life in ecclesiastic fidelity, he was witness and, from that position he contributed to the universal Church showing the particular picture of Latin America.